2011
DOI: 10.5577/intdentres.2011.vol1.no1.2
|View full text |Cite
|
Sign up to set email alerts
|

The Gingival Crevicular Fluid Levels of IL-1β, IL-6 and TNF-α in Late Adult Rats

Abstract: Aim: To evaluate the levels of interleukin1β (IL-1β), interleukin 6 (IL-6) and tumor necrosis factor alpha (TNF-α) in the samples of gingival crevicular fluid (GCF) taken from the late adult rats during the orthodontic tooth movement and to evaluate the responses to orthodontic treatment . Methodology: In experiment 19 adult (120 days) Spraque-Dawley rats were used. Approximately 15 g force applying open coil spring was applied actively between the upper incisors of the rats. Before and after the activation on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 39 publications
0
3
0
Order By: Relevance
“…This finding was in accordance with that of Basaran ( 22 ) and Ozcun ( 23 ) who reported no significant alterations in the level of pro-inflammatory cytokines following initiation of orthodontic treatment. However, in the study by Kaya et al, levels of IL-6 and TNFα reached their maximum at three days in rats and then started to decrease from days seven and 10 onwards ( 18 ). Ren et al showed that the level of IL-6 and TNFα significantly increased at 24 hours, and during the linear phase of OTM, concentration of these cytokines decreased almost to the baseline level ( 24 ).…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…This finding was in accordance with that of Basaran ( 22 ) and Ozcun ( 23 ) who reported no significant alterations in the level of pro-inflammatory cytokines following initiation of orthodontic treatment. However, in the study by Kaya et al, levels of IL-6 and TNFα reached their maximum at three days in rats and then started to decrease from days seven and 10 onwards ( 18 ). Ren et al showed that the level of IL-6 and TNFα significantly increased at 24 hours, and during the linear phase of OTM, concentration of these cytokines decreased almost to the baseline level ( 24 ).…”
Section: Discussionmentioning
confidence: 97%
“…Knowledge about chemical biomarkers, which indicate changes in bone remodeling, inflammation and root resorption, can help determine the exact amount of load and its duration of application required for each tooth, select the most efficient treatment plan with minimal complications and accelerate the treatment course ( 17 ). Most studies ( 18 , 13 ) did not compare the level of cytokines at the tensile and pressure side, and in some studies ( 5 , 16 ) both sides were compared, but these studies reported contradictory results. Also, most studies ( 18 , 19 ) examined the cytokines level one day after force application.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation